A biodegradable synthetic graft for small arteries matches the performance of autologous vein in rat carotid arteries. (October 2018) - Lee, Kee-Won; Gade, Piyusha S.; Dong, Liwei; Zhang, Zhaoxiang; Aral, Ali Mubin; Gao, Jin; Ding, Xiaochu; Stowell, Chelsea E.T.; Nisar, Muhammad Umer; Kim, Kang; Reinhardt, Dieter P.; Solari, Mario G.; et al.
Abstract: Autologous veins are the most widely used grafts for bypassing small arteries in coronary and peripheral arterial occlusive diseases. However, they have limited availability and cause donor-site morbidity. Here, we report a direct comparison of acellular biodegradable synthetic grafts and autologous veins as interposition grafts of rat carotid arteries, which is a good model for clinically relevant small arteries. Notably, extensive but transient infiltration of circulating monocytes at day 14 in synthetic grafts leads to a quickly-resolved inflammation and arterial-like tissue remodeling. The vein graft exhibits a similar inflammation phase except the prolonged presence of inflammatory monocytes. The walls of the remodeled synthetic graft contain many circumferentially aligned contractile non-proliferative smooth muscle cells (SMCs), collagen and elastin. In contrast, the walls of the vein grafts contain disorganized proliferating SMCs and thicken over time, suggesting the onset of stenosis. At 3 months, both grafts have a similar patency, extracellular matrix composition, and mechanical properties. Furthermore, synthetic grafts exhibit recruitment and re-orientation of newly synthesized collagen fibers upon mechanical loading. To our knowledge, this is the first demonstration of a biodegradable synthetic vascular graft with a performance similar to an autologous vein in small artery grafting.